The wandering « Leg of an Indian King ». The cultural biography of a friction idiophone now in the Pigorini Museum in Rome, Italy - Davide Domenici (Journal de la Société des Américanistes)
The article presents new data on the history of a Mesoamerican musical instrument, which is a notched human bone used as a friction idiophone, today, held at the Pigorini Museum in Rome, Italy, where it is recorded as MNPE n. 4209. The documentary data allow for the reconstruction of the instrument’s cultural biography along a time span of almost five centuries. Collected in the Mixtec Kingdom of Tututepec (Oaxaca, Mexico) during the 16th century, it passed through different Italian collections before reaching its present location in Rome toward the end of the 19th century. The text also analyzes how in its long historical journey through different contexts and regimes of value, the notched bone generated diverse sets of discourses on cultural otherness. It is argued that this discursive agency of the object is due to its enduring coevalness, a quality that allows ancient objects to be always contemporary and meaningful to different cultural audiences.